Protein crystallization and structure determination at room temperature in the CrystalChip - Petr Pachl; Léna Coudray; Romain Vincent; Léa Nilles; Hélène Scheer; Christophe Ritzenthaler; Adéla Fejfarová; Pavlína Řezáčová; Sylvain Engilberge; Claude Sauter (FEBS Open Bio)
The production of high‐quality crystals is a key step in crystallography in general, but control of crystallization conditions is even more crucial in serial crystallography, which requires sets of crystals homogeneous in size and diffraction properties. This protocol describes the implementation of a simple and user‐friendly microfluidic device that allows both the production of crystals by the counter‐diffusion method and their in situ analysis by serial crystallography. As an illustration, the whole procedure is used to determine the crystal structure of three proteins from data collected at room temperature at a synchrotron radiation source.